Savings in internal logistics using a RFID-based software system in a lean context - Freitas, Ana C. (2017)
Raw material traceability in internal flows is essential for the logistics management, allowing a better material process planning and an improved real-time trace. In fact, logistics planners need to track and trace raw material throughout the internal replenishment process, including the reception and storing processes. In this research, it is proposed a software system that integrates RFID technologies and information for internal logistics in a lean context named "Smart Internal Supply Chain" (SISC). Misplacement of material, line stoppages, unattended material turning outdated and obsolete, are some examples of the problems that can be mitigated using the proposed solution. This paper also discusses the prospective impact of SISC implementation and the expected results in terms of productivity improvement. The benefit of using RFID in the internal supply chain is evidenced, increasing the efficiency and productivity of processes up to 50% and consequently, saving logistics costs.